(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Ernest Miller Hemingway (1899-1961), a leading American iconoclast, aimed to depict human conflicts by disseminating various symbols and signs in his seminal 1951 work, "The Old Man and the Sea." For this remarkable work, Hemingway was honored with the Pulitzer Prize in 1953 and the Nobel Prize in 1954. The author hopes to construct a metaphor for the human condition through Santiago, a Cuban fisherman, and the novella’s protagonist. Santiago’s trials show how human beings may thrive under extreme conditions. Having found the source of his greatness and resolve in the depths of the sea, Santiago is the embodiment of harsh reality. It will be represented here as the unconquerable fighter of nature. Like Hemingway, he takes great pride in defying death and destruction by persevering through the ordeal and keeping up with the times. However, the purpose of this further research is to delve deeper into the author’s symbolic and lyrical choices.